Second Chorus - Potter, Henry C.; Sparkuhl, Theodor; Astaire, Fred; Goddard, Paulette; Butterworth, Charles (ZYX Music, 2017)
"Second Chorus" is a 1940 Hollywood musical comedy film starring Paulette Goddard and Fred Astaire and featuring Artie Shaw, Burgess Meredith and Charles Butterworth, with music by Artie Shaw, Bernie Hanighen and Hal Borne, and lyrics by Johnny Mercer. The film was directed by H.C. Potter and produced independently for Paramount Pictures by Boris Morros, with associate producers Robert Stillman and Fred Astaire ... In a 1968 interview, Astaire described this effort as "the worst film I ever made." Astaire admitted that he was attracted to the film by the opportunity to "dance-conduct this real swingin' outfit". In an interview shortly before his death, Artie Shaw admitted this film put him off acting. [wikipedia.org]
Keywords: DVD-Video